BAGAIMANA MODEL MEANS END ANALYSIS (MEA) MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA BERDASARKAN SELF CONFIDENCE? - Hemadwi Cahya, Devhita; Revita, Rena; Azmi, Memen Permata (ALGORITMA: Journal of Mathematics Education, 2024)
AbstractMathematical communication ability is one of the abilities students must have to solve mathematical problems. This study aims to analyze the effect of the means-end analysis learning model on students' mathematical communication skills in terms of self-confidence. The experimental research used a factorial experimental design. The population of this research is grade XI students at one of the SMAN in Kerinci, as many as 6 classes. The sampling technique used cluster random sampling, class XI.4 as the experimental class and class XI.3 as the control class. Data collection techniques include a mathematical communication skills test and a self-confidence questionnaire. The data analysis technique used descriptive analysis and a two-way ANOVA test. The results showed differences in mathematical communication skills between students who followed the means-end analysis learning model and students who followed the Direct learning model. There were differences in mathematical communication skills between students who had high, medium, and low self-confidence, and there was no interaction effect between the means-end analysis learning model and self-confidence on students' mathematical communication skills. Abstrak Kelmampulan komulnikasi matelmatis menjadi salah satu kemampuan yang harus dimiliki siswa untuk melnyellelsaikan permasalahan matelmatis. Penelitian ini bertujuan untuk menganalisis pengaruh model pembelajaran means end analysisterhadap kemampuan komunikasi matematis siswa ditinjau dari self confidence. Penelitian eksperimen menggunakan factorial eksperiment design. Populasi penelitian ini siswa kelas XI di salah satu SMAN di Kerinci sebanyak 6 kelas. Teknik pengambilan sampel menggunakan cluster random sampling, kelas XI.4 sebagai kelas eksperimen dan kelas XI.3 sebagai kelas kontrol. Teknik pengumpulan data berupa tes kemampuan komunikasi matematis dan angket self confidence. Teknik analisis data menggunakan analisis deskriptif dan uji anova dua arah. Hasil penelitian menunjukkan terdapat perbedaan kemampuan komunikasi matematis antara siswa yang mengikuti model pembelajaran means end analysisdengan siswa yang mengikuti model pembelajaran Langsung, terdapat perbedaan kemampuan komunikasi matematis antara siswa yang memiliki self confidence tinggi, sedang, dan rendah, dan tidak terdapat pengaruh interaksi antara model pembelajaran means end analysis dan self confidence terhadap kemampuan komunikasi matematis siswa.